Substituent‐Controlled Energetics and Barriers of Mechanochromic Spiropyran‐Functionalized Poly(ɛ‐caprolactone). Issue 1 (7th October 2022) - Kempe, Fabian; Metzler, Lukas; Brügner, Oliver; Buchheit, Hannah; Walter, Michael; Komber, Hartmut; Sommer, Michael
Abstract: In a joint theoretical and experimental study, it is shown that the onset of the mechanically‐induced spiropyran (SP) to merocyanine (MC) isomerization can be controlled by both the regiochemistry and the substitution pattern of SP. Four SP‐based bifunctional initiators with consistently varied polymer chain anchor point and substituent are used to synthesize poly‐ ε ‐caprolactone (PCL). Theoretical calculations (1S and 3S COGEF methods) and in‐situ visible light absorption measurements of films during uniaxial stress–strain experiments consistently show varying activation barriers of the force‐induced ring‐opening reaction of SP to give MC. SPs with PCL chains attached in ortho ‐position to the pyran oxygen isomerize at lower stress than their para ‐analogs. NO2 ‐substituted SP mechanophores exhibit a lower activation barrier compared with H‐substituted ones, but only if the NO2 substituent is located in para ‐position relative to the O at the pyran half. These results are consistent with theoretical loading rate‐dependent rupture forces required to break the CO bond of SP and may guide mechanophore design. Abstract : Four different spiropyrans with consistently varying substitution patterns are incorporated into the middle of poly( ε ‐caprolactone) used for tensile testing with in‐situ UV–vis spectroscopy. The influence of combined electronic and steric effects on the force‐induced spiropyran–merocyanine transition is investigated theoretically and experimentally by looking at onset of color formation, barrier heights, and rupture forces.